Analisis Sikap dan Kepuasan Petani dalam Menggunakan Benih Kelapa Sawit (Elaeis guineensis) Bersertifikat di Kabupaten Labuhan Batu Utara - Myrna Pratiwi Nasution; Laura Juita Pinem (Fakultas Pertanian, Universitas Timor, 2020)
Palm oil farming productivity is largely determinate by seed quality. The growing importance of the use of good quality seed to palm oil production encourages farmer to be more critical in choosing variety of palm oil seed. Attitude dan satisfaction of farmer in using certified palm oil seed is important to understand what the farmer want in farming activities. This research is designed to observe it. The attitudes of farmers were analyzed using fishbein multiatribut approach while customers satisfied using Important Performance Analysis (IPA) and Customer Satisfied Index (CSI). Based on this research, attributes that affect farmers in using certified seed palm oil are production potential, seed endurance, plant age, seed viability, efficient in use fertilizers, variety, seed size, seed certified label, seed price, fresh fruit bunch price, seed location, seed availability, ease of selling fresh bunch price, and shop promotion. Fishbein multivariate analysis show that neutral attitudes on certified palm oil seed (76 percent). While result CSI on certified palm oil seed are satisfied 70.04 percent farmers.